A brief history of fetal echocardiography and its impact on the management of congenital heart disease. Issue 12 (29th December 2017) - Maulik, Dev; Nanda, Navin C.; Maulik, Devika; Vilchez, Gustavo
Abstract : Congenital heart disease (CHD), the most common congenital malformation, is associated with adverse outcome. Development of fetal echocardiography has made prenatal diagnosis of CHD a reality, and in the process revolutionized its management. This historical review briefly narrates this development over the decades focusing on the emergence of the primary modalities of fetal echocardiography comprised of the time‐motion mode, two‐dimensional B‐mode, spectral Doppler, color Doppler, and three‐ and four‐dimensional cardiac imaging. Collaboration between clinicians and engineers has been central to these advances. Also discussed are the accuracy and impact of fetal echocardiography on the management of CHD, and especially its role in the prenatal diagnosis of critical CHD in individualizing the management and improving the outcome. Despite these advances, most cases of CHD are not identified prenatally, emphasizing the continuing need for further technological and educational innovation and improvement.